Concrete member

JP2025042307APending Publication Date: 2025-03-27TAKENAKA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023149242
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-27

Smart Images

  • Figure 2025042307000001_ABST
    Figure 2025042307000001_ABST
Patent Text Reader

Abstract

To provide a concrete member capable of enhancing manufacturability and usability of a concrete member.SOLUTION: A concrete member 1 constitutes a structure, includes at least water, a cement material, an aggregate, an additive, an organic fiber material, and a steel fiber material, where a water cement ratio that is a mixture ratio of water and a cement material is set to e.g., 22% to 40%, a unit weight of the steel fiber material is set to, e.g., 38.75 kg / m3 to 77.5 kg / m3, and a unit weight of the organic fiber material is set to 1.0 kg / m3 or over.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a concrete member. [Background technology]

[0002] As one of the concrete members that can exhibit high strength, a concrete member made of concrete containing cement, fine particles, inorganic particles (e.g., quartz powder), aggregate, metal fibers, a water-reducing agent, and water has been proposed (for example, see Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-223761 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been an increasing need to improve the workability and durability of concrete members. However, in the above-mentioned conventional concrete members, only the mix ratios for improving the strength of various materials are disclosed, and there is a risk that the workability and / or durability of the concrete member will decrease, resulting in a decrease in the manufacturability and usability of the concrete member. Therefore, there is room for improvement in terms of improving the manufacturability and usability of the concrete member.

[0005] The present invention has been made in consideration of the above, and has an object to provide a concrete member that makes it possible to improve the manufacturability and usability of the concrete member. [Means for solving the problem]

[0006] In order to solve the above-mentioned problems and achieve the object, the concrete member described in claim 1 is a concrete member constituting a structure, and includes at least water, cement material, aggregate, admixture, organic fiber material, and steel fiber material, the water-cement ratio, which is the mixture ratio of the water and the cement material, being about 22% to 40%, and the unit weight of the steel fiber material being 38.75 kg / m 3 from 77.5 kg / m 3 That was the extent of it.

[0007] The concrete member according to claim 2 is the concrete member according to claim 1, wherein the unit weight of the organic fiber material is 1.0 kg / m 3 That's all.

[0008] The concrete member according to claim 3 is the concrete member according to claim 1 or 2, wherein the unit weight of the admixture is 3.0 kg / m 3 from 12.24 kg / m 3 That was the extent of it.

[0009] The concrete member according to claim 4 is the concrete member according to claim 1 or 2, further comprising an adhesion improver for improving adhesion of the cement material to the organic fiber material and / or the steel fiber material, and the unit weight of the adhesion improver is 7.5 kg / m 3 from 198 kg / m 3 That was the extent of it.

[0010] The concrete member according to claim 5 is the concrete member according to claim 4, wherein the adhesion improving material is silica fume which constitutes a part of the cement material, the water-cement ratio is about 22%, and the unit weight of the steel fiber material is 38.75 kg / m 3 The unit weight of the admixture is about 9 kg / m 3 from 12.44 kg / m 3 The unit weight of the silica fume is about 22.5 kg / m 3 from 37.5 kg / m 3 That was the extent of it.

[0011] The concrete member according to claim 6 is the concrete member according to claim 4, wherein the adhesion improver is silica sand which constitutes a part of the aggregate, the water-cement ratio is about 35%, and the unit weight of the steel fiber material is 54.6 kg / m 3 The unit weight of the admixture is about 3.7 kg / m 3 The unit weight of the silica sand is about 198 kg / m 3 That was the extent of it.

[0012] A concrete member according to a seventh aspect of the present invention is the concrete member according to the first or second aspect, wherein the steel fiber material includes plated steel fibers and / or stainless steel fibers. Effect of the Invention

[0013] According to the concrete member of claim 1, the concrete member contains at least water, cement material, aggregate, admixture, organic fiber material, and steel fiber material, the water-cement ratio, which is the mixture ratio of the water and the cement material, is about 22% to 40%, and the unit weight of the steel fiber material is 38.75 kg / m 3 from 77.5 kg / m 3 Therefore, as the test results described later show, it is possible to improve the workability and durability of the concrete member, and it is possible to improve the manufacturability and usability of the concrete member.

[0014] According to the concrete member of claim 2, the unit weight of the organic fiber material is set to 1.0 kg / m 3 Since the above is the case, other unit weights (specifically, 1.0 kg / m 3 In comparison with a concrete member having a high temperature resistance (less than 1000° C.), the decrease in the strength of the concrete member at high temperatures can be suppressed, and the fire resistance of the concrete member can be improved.

[0015] According to the concrete member of claim 3, the unit weight of the admixture is set to 3.0 kg / m 3 from 12.24 kg / m 3 Therefore, the test results described later show that compared with other unit weights, the workability of the concrete member can be improved, and the manufacturability of the concrete member can be improved.

[0016] According to the concrete member of claim 4, the unit weight of the adhesion improving material is set to 7.5 kg / m 3 from 198 kg / m 3 Therefore, even when the water-cement ratio is relatively low, the adhesion of the cement material to the organic fiber material and / or the steel fiber material can be improved, and the strength of the concrete member can be increased.

[0017] According to the concrete member described in claim 5, the adhesion improving material is silica fume, the water-cement ratio is about 22%, and the unit weight of the steel fiber material is 38.75 kg / m 3 The unit weight of the admixture is set at 9 kg / m 3 from 12.44 kg / m 3 The unit weight of silica fume is set at 22.5 kg / m 3 from 37.5 kg / m 3 Therefore, the test results described later show that when the adhesion improving agent is silica fume, the workability and durability of the concrete member can be improved, and the manufacturability and usability of the concrete member can be improved.

[0018] According to the concrete member described in claim 6, the adhesion improving material is silica sand, the water-cement ratio is about 35%, and the unit weight of the steel fiber material is 54.6 kg / m 3 The unit weight of the admixture is set at 3.7 kg / m 3 The unit weight of the silica sand is set at 198 kg / m 3 Therefore, the test results described later show that when the adhesion improving agent is silica sand, the workability and durability of the concrete member can be improved, and the manufacturability and usability of the concrete member can be improved.

[0019] According to the concrete member described in claim 7, the steel fiber material contains plated steel fibers and / or stainless steel fibers, so that deterioration of the steel fiber material due to corrosion, etc. can be suppressed compared to other materials, and the function of the steel fiber material can be maintained. [Brief description of the drawings]

[0020] [Figure 1] 1 is a perspective view showing an overview of a concrete member according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along the line AA in FIG. [Diagram 3] FIG. 2 is a diagram showing details of the configuration of various concrete members used in the workability confirmation test. [Figure 4] FIG. 13 is a diagram showing the test results of a workability confirmation test. [Diagram 5] FIG. 13 is a diagram showing test results of a durability confirmation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the concrete member according to the present invention will be described in detail with reference to the accompanying drawings. First, [I] the basic concept of the embodiment will be described, then [II] specific contents of the embodiment will be described, and finally, [III] modified examples of the embodiment will be described. However, the present invention is not limited to the embodiment.

[0022] [I] Basic Concept of the Embodiment First, a basic concept of the embodiment will be described. The embodiment generally relates to a concrete member that constitutes a structure.

[0023] Here, the specific structure and type of the "structure" are arbitrary, but the concept includes, for example, architectural structures such as office buildings, commercial facilities, public facilities, and collective housing such as apartments and condominiums, as well as civil engineering structures such as bridges and tunnels, but in the embodiment, it will be described as an office building having multiple floors.

[0024] In addition, the specific type of "concrete member" is arbitrary, but the concept includes, for example, non-structural members made of concrete (one example is a concrete partition material (specifically, an exterior material such as a front panel material, and an interior material such as a back panel material)) and structural members made of concrete (one example is a concrete wall material, floor material, pillar material, beam material, etc.), but in the embodiment, it will be described as an exterior material made of concrete.

[0025] [II] Specific Contents of the Embodiments Next, the specific contents of the embodiment will be described.

[0026] (composition) First, the configuration of the concrete member according to the embodiment will be described.

[0027] In the following explanation, the X direction in Figure 1 is referred to as the left-right direction of the concrete member (the -X direction is the left direction of the concrete member, and the +X direction is the right direction of the concrete member), the Y direction in Figure 1 is referred to as the front-to-back direction of the concrete member (the +Y direction is the front direction of the concrete member, and the -Y direction is the rear direction of the concrete member), and the Z direction in Figure 1 is referred to as the up-down direction of the concrete member (the +Z direction is the upward direction of the concrete member, and the -Z direction is the downward direction of the concrete member).

[0028] The concrete member 1 is a component (specifically, a concrete exterior material) that constitutes a structure (specifically, an office building having multiple floors) not shown in the figure, and at least one of them is erected between the floor materials of the structure.

[0029] Furthermore, the specific shape and size of the concrete member 1 are arbitrary, but in the embodiment, they may be set as follows.

[0030] That is, the front shape of the concrete member 1 is set to be substantially rectangular.

[0031] Furthermore, the length (width) in the left-right direction of the concrete member 1 is set to about 1500 mm to 2000 mm. However, without being limited thereto, for example, it may be set to less than 1500 mm, or may be set to more than 2000 mm.

[0032] The length (thickness) of the concrete member 1 in the front-rear direction is set to about 100 mm to 200 mm. However, it is not limited to this and may be set to less than 100 mm or more than 200 mm, for example.

[0033] Furthermore, the length (height) in the vertical direction of the concrete member 1 is set to about 3500 mm to 4000 mm. However, without being limited to this, it may be set to less than 3500 mm, or may be set to exceed 4000 mm, for example.

[0034] Furthermore, the concrete member 1 may have any specific configuration, but in this embodiment, as shown in FIGS. 1 and 2, the concrete member 1 includes a main body 10 and a reinforcing bar 20. As shown in FIG.

[0035] (Configuration - Main body) The main body 10 is a basic constituent of the concrete member 1, and is configured to include water, cement material, aggregate, admixture, organic fiber material, steel fiber material, and an adhesion improving material (all of which are omitted from the illustration).

[0036] (Configuration - Main body - Water) The water is, for example, tap water and / or water other than tap water (eg, well water, distilled water, purified water, etc.).

[0037] (Structure - Main body - Cement material) The cement material is composed of, for example, known Portland cement (e.g., ordinary Portland cement, high-early-strength Portland cement, moderate-heat Portland cement, etc.), known blended cement (e.g., blast-furnace cement, fly ash cement, etc.), and / or known special cement (e.g., silica fume cement, ecocement, alumina cement, etc.).

[0038] Furthermore, the method for setting the mixture ratio of water and cement material in the concrete member 1 (hereinafter referred to as the "water-cement ratio") is arbitrary, but in the embodiment, from the viewpoint of improving the workability and durability of the concrete member 1, it is set to approximately 22% to 40% based on the test results described below.

[0039] (Structure - Main body - Aggregate) The aggregate includes fine aggregate and coarse aggregate.

[0040] (Structure - Main body - Aggregate - Fine aggregate) The fine aggregate is formed using, for example, known fine aggregate (for example, natural aggregate (e.g., river sand, mountain sand, sea sand, crushed stone, crushed sand, etc.), artificial aggregate (e.g., blast furnace slag fine aggregate, etc.), recycled aggregate (e.g., concrete waste, etc.).

[0041] The method of setting the unit weight of the fine aggregate in the concrete member 1 is arbitrary, but in this embodiment, it is set to 250 kg / m 3 from 800kg / m 3 However, it is not limited to this, for example, 250 kg / m 3 It may be set to less than 800 kg / m 3 It may be set to be greater than

[0042] (Composition - Main body - Aggregate - Coarse aggregate) The coarse aggregate is formed using, for example, known coarse aggregate (eg, river gravel, sea gravel, mountain gravel, crushed stone, slag crushed stone, etc.).

[0043] The method for setting the unit weight of the coarse aggregate in the concrete member 1 is arbitrary, but in this embodiment, it is set to 600 kg / m 3 to 700 kg / m 3 However, it is not limited to this, for example, 600 kg / m 3 It may be set to less than 700 kg / m 3 It may be set to be greater than

[0044] (Configuration - Main body - Admixture) The admixture is intended to enhance various functions of the concrete member 1, and is constituted by using, for example, a known admixture (one example is a water-reducing agent such as a high-performance water-reducing agent).

[0045] The method of setting the unit weight of the admixture in the concrete member 1 is arbitrary, but in the embodiment, it is set to 3.0 kg / m based on the test results described later. 3 from 12.24 kg / m 3 It is set to a certain extent.

[0046] This allows the workability of the concrete member 1 to be improved compared to other unit weights, and allows the manufacturability of the concrete member 1 to be improved.

[0047] However, this is not limited to this, for example, 3.0 kg / m 3 It may be set to less than 12.24 kg / m 3 It may be set to be greater than

[0048] (Structure - Main body - Organic fiber material) The organic fiber material is intended to improve the fire resistance of the concrete member 1, and is made of, for example, a known organic fiber material (one example is a resin fiber material such as polypropylene fiber).

[0049] The method for setting the unit weight of the organic fiber material in the concrete member 1 is arbitrary, but in the embodiment, it is set to 1.0 kg / m based on the test results described later. 3 It is set to above.

[0050] This allows other unit weights (specifically, 1.0 kg / m 3 In comparison with a concrete member having a high temperature resistance (less than 1000° C.), it is possible to suppress a decrease in the strength of the concrete member under high temperature conditions, and it is possible to improve the fire resistance of the concrete member 1.

[0051] However, this is not limited to this, for example, 1.0 kg / m 3 It may be set to less than

[0052] (Structure - Main body - Steel fiber material) The steel fiber material is intended to improve the strength (e.g., compressive strength, bending strength, etc.) of the concrete member 1. This steel fiber material is made of, for example, a known steel fiber material, specifically, made of plated steel fiber and / or stainless steel fiber (more specifically, made of plated steel fiber).

[0053] This makes it possible to suppress deterioration of the steel fiber material due to corrosion and the like compared to other materials, and allows the functionality of the steel fiber material to be maintained.

[0054] However, the present invention is not limited to this, and may be configured using, for example, a steel fiber material other than plated steel fiber and stainless steel fiber (one example is non-plated steel fiber).

[0055] In addition, the method of setting the unit weight of the steel fiber material in the concrete member 1 is arbitrary, but in the embodiment, the concrete member 1 is designed to have high strength (for example, bending strength of 9 N / mm 2 Based on the test results described below, 3 from 77.5 kg / m 3 It is set to a certain extent.

[0056] (Configuration - Main body - Adhesion improvement material) The adhesion improver is intended to improve the adhesion of the cement material to the organic fiber material and / or the steel fiber material. This adhesion improver is made of, for example, a known adhesion improver (one example is an adhesion improver containing SiO2). Specifically, it is made of silica fume that constitutes a part of the cement material, or made of silica sand that constitutes a part of the aggregate (specifically, fine aggregate).

[0057] The method for setting the unit weight of the adhesion improving material is arbitrary, but in the embodiment, it is set to 7.5 kg / m based on the test results described later. 3 from 37.5 kg / m 3 It is set to a certain extent.

[0058] As a result, even when the water-cement ratio is relatively low, the adhesion of the cement material to the organic fiber material and / or the steel fiber material can be improved, and the strength of the concrete member can be increased.

[0059] However, this is not limited to this, for example, 7.5 kg / m 3 It may be set to less than 37.5 kg / m 3 It may be set to be greater than

[0060] In addition, when the adhesion improving material is silica fume, from the viewpoint of improving the workability and durability of the concrete member 1, it is desirable to set the various materials of the concrete member 1 as follows, based on the test results described below.

[0061] Specifically, based on the test results described later, the water-cement ratio is set to about 22%. Also, the unit weight of the steel fiber material in the concrete member 1 is set to 38.75 kg / m 3 The unit weight of the admixture in the concrete member 1 is set to about 9 kg / m 3 from 12.44 kg / m 3 The unit weight of the silica fume in the concrete member 1 is set to about 22.5 kg / m 3 from 37.5 kg / m 3 Set it to a certain extent.

[0062] By setting in this way, when the adhesion improving agent is silica fume, it is possible to improve the workability and durability of the concrete member 1, and it is possible to improve the manufacturability and usability of the concrete member 1.

[0063] In addition, when the adhesion improving material is silica sand, from the viewpoint of improving the workability and durability of the concrete member 1, it is desirable to set the various materials of the concrete member 1 as follows, based on the test results described below.

[0064] Specifically, based on the test results described later, the water-cement ratio is set to about 35%. Also, the unit weight of the steel fiber material in the concrete member 1 is set to 54.6 kg / m 3 The unit weight of the admixture in the concrete member 1 is set to about 3.7 kg / m 3 The unit weight of the silica sand in the concrete member 1 is set to about 198 kg / m 3 Set it to a certain extent.

[0065] With such settings, when the adhesion improving agent is silica sand, the workability and durability of the concrete member 1 can be improved, and the manufacturability and usability of the concrete member 1 can be improved.

[0066] (Structure - Reinforcement) Returning to Fig. 1, the reinforcing bars 20 are for reinforcing the concrete member 1. The reinforcing bars 20 are formed, for example, using known long reinforcing bars (as one example, different diameter reinforcing bars), and as shown in Fig. 1 and Fig. 2, a plurality of reinforcing bars 20 are arranged side by side substantially along the left-right direction and the up-down direction inside the main body 10 so that the front shape is substantially lattice-like. However, the reinforcing bars 20 are not limited to this, and may be arranged in a manner other than the above, for example.

[0067] The concrete member 1 as described above can improve the workability and durability of the concrete member 1, and can also improve the manufacturability and usability of the concrete member 1.

[0068] (Method of manufacturing concrete components) Next, a method for manufacturing the concrete member 1 will be described.

[0069] The manufacturing method according to the embodiment includes a first mixing step, a second mixing step, a pouring step, and a curing step.

[0070] (Concrete component manufacturing method - First mixing process) First, the first kneading step will be described.

[0071] The first mixing step is a step of mixing water, cement material, aggregate, admixture, and adhesion promoter.

[0072] Specifically, water, cement material, aggregate, admixture, and adhesion improver are charged into the storage section of a known mixer (e.g., a two-shaft mixer), and the water, cement material, aggregate, admixture, and adhesion improver are then mixed by the mixer for a predetermined time (e.g., about 2 minutes).

[0073] (Concrete component manufacturing method - second mixing process) Next, the second kneading step will be described.

[0074] The second mixing step is a step of further adding and mixing an organic fiber material and a steel fiber material after the first mixing step.

[0075] Specifically, the organic fiber material and steel fiber material are charged into the storage section of the mixer, and then the water, cement material, aggregate, admixture, adhesion enhancer, organic fiber material, and steel fiber material are mixed in the mixer for a predetermined time (e.g., about 15 minutes).

[0076] (Concrete component manufacturing method - casting process) Next, the casting process will be described.

[0077] The casting process is a process that follows the second mixing process and involves pouring the materials mixed in the second mixing process (specifically, water, cement materials, aggregates, admixtures, adhesion enhancers, organic fiber materials, and steel fiber materials) into a formwork.

[0078] Specifically, first, a known formwork (e.g., a wooden formwork) is assembled, and then reinforcing bars 20 are arranged in the formwork. Next, the mixture mixed in the second mixing step is poured into the formwork using a known tool. Thereafter, the poured mixture is left as it is for a predetermined period of time (e.g., about 1 to 10 days) in a predetermined environment until it hardens, thereby forming the concrete member 1.

[0079] (Manufacturing method of concrete components - curing process) Next, the curing process will be described.

[0080] The curing step is a step of curing the concrete member 1 after the pouring step.

[0081] Specifically, first, the concrete member 1 is removed from the formwork. Thereafter, the concrete member 1 that has been removed from the formwork is cured in a predetermined environment for a predetermined period of time (for example, about 30 days).

[0082] By using the above-described manufacturing method, the concrete member 1 can be manufactured with high precision.

[0083] (Test results for workability and durability) Next, the results of various tests conducted by the applicant will be described. Here, the results of the workability confirmation test and the durability confirmation test will be described.

[0084] (Test results of workability confirmation test and durability confirmation test - Workability confirmation test - Overview) First, an overview of the workability verification test will be given.

[0085] The workability confirmation test is a test to confirm the workability of various concrete components.

[0086] (Test results of workability confirmation test and durability confirmation test - Workability confirmation test - Overview - Test method) The test method for this workability confirmation test is carried out as follows using a known slump test method (for example, the test method of JISA1101, etc.).

[0087] That is, first, pre-hardened concrete corresponding to various concrete components (i.e., fresh concrete mixed with water, cement materials, admixtures, aggregates, organic fiber materials, steel fiber materials, and / or adhesion improving materials) is placed in a known slump cone and stirred a predetermined number of times with a ram. Next, the height of the pre-hardened concrete is measured. Next, after the slump cone is lifted, the height of the pre-hardened concrete is also measured. Then, whether or not the workability is excellent is judged based on whether or not the difference in height measured before and after lifting the slump cone is equal to or greater than a threshold value (specifically, 12 cm).

[0088] (Test results of workability confirmation test and durability confirmation test - Workability confirmation test - Overview - Details of the composition of various concrete components) In addition, the various concrete members (specifically, the concrete members excluding the reinforcing bars 20) used in the workability confirmation test are divided into 10 types as shown in Figure 3 (hereinafter referred to as the "first concrete member" to the "tenth concrete member").

[0089] In addition, the various concrete components are composed of water, cement materials, admixtures, aggregates, organic fiber materials, steel fiber materials, and / or adhesion improvers, and the unit weight of the aggregates is set to the same amount as the above unit weights.

[0090] As shown in Fig. 3, the first concrete member has a water-cement ratio of 35%, an unknown unit weight of admixture, and an unknown unit weight of organic fiber material. 3 , unit weight of steel fiber material = 108 kg / m 3 , unit weight of adhesion improver = 0 kg / m 3, Type of cement = Ordinary Portland cement is used.

[0091] The second concrete member had a water-cement ratio of 35% and a unit weight of admixture of 4.23 kg / m 3 , unit weight of organic fiber material = 0 kg / m 3 , unit weight of steel fiber material = 77kg / m 3 , unit weight of adhesion improver = 0 kg / m 3 It is composed of:

[0092] The third concrete member had a water-cement ratio of 35% and a unit weight of admixture of 3.85 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 77.5 kg / m 3 , unit weight of adhesion improver = 0 kg / m 3 , Cement material type = ordinary Portland cement.

[0093] The fourth concrete member had a water-cement ratio of 35% and a unit weight of admixture of 3.7 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 77kg / m 3 , unit weight of adhesion improver = 197 kg / m 3 (In Figure 3, "197 kg / m 3 It is composed of the following materials: silica sand (silica sand) and ordinary Portland cement.

[0094] The fifth concrete member had a water-cement ratio of 35% and a unit weight of admixture of 3 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 55kg / m 3 , unit weight of adhesion improver = 0 kg / m 3 , Cement material type = ordinary Portland cement.

[0095] The sixth concrete member had a water-cement ratio of 35% and a unit weight of admixture of 3.7 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 54.6 kg / m 3 , Unit weight of adhesion improver (silica sand) = 198 kg / m 3 (In Figure 3, "198 kg / m 3 It is composed of the following materials: silica sand (silica sand) and ordinary Portland cement.

[0096] The seventh concrete member had a water-cement ratio of 30% and a unit weight of admixture of 3.5 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 55kg / m 3 , unit weight of adhesion improver = 0 kg / m 3 , Cement material type = ordinary Portland cement.

[0097] The eighth concrete member had a water-cement ratio of 22% and a unit weight of admixture of 9 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 38.75 kg / m 3 , Unit weight of adhesion improver (silica fume) = 7.5 kg / m 3 (In Figure 3, "7.5 kg / m 3 It is composed of the following cement materials: (Silica fume) and mixed cement and silica fume cement.

[0098] The 9th concrete member had a water-cement ratio of 22% and a unit weight of admixture of 9 to 12.44 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 38.75 kg / m 3 , Unit weight of adhesion improver (silica fume) = 22.5-37.5 kg / m 3 (In Figure 3, "22.5 to 37.5 kg / m 3It is composed of the following cement materials: ordinary Portland cement and silica fume cement.

[0099] The 10th concrete member had a water-cement ratio of 40% and a unit weight of admixture of 3.01 kg / m 3 , unit weight of organic fiber material = 1 kg / m 3 , unit weight of steel fiber material = 54.6 kg / m 3 , Unit weight of adhesion improver (silica sand) = 204 kg / m 3 (In Figure 3, "204 kg / m 3 It is composed of the following materials: silica sand (silica sand) and ordinary Portland cement.

[0100] (Test results of workability confirmation test and durability confirmation test - Workability confirmation test - Details of test results) Next, the details of the test results of the workability verification test will be explained.

[0101] As shown in Figure 4, the slump values ​​of the first to third concrete members were below the threshold, but the slump values ​​of the fourth to tenth concrete members were above the threshold. This confirmed that the fourth to tenth concrete members had excellent workability.

[0102] (Test results of workability confirmation test and durability confirmation test - Durability confirmation test - Overview) Next, an outline of the durability confirmation test will be described.

[0103] The durability confirmation test is a test for confirming the durability of various concrete members.

[0104] (Test results of workability confirmation test and durability confirmation test - Durability confirmation test - Overview - Test method) The durability confirmation test is carried out as follows using a known drying shrinkage test method.

[0105] That is, first, various concrete members formed to a predetermined size (specifically, 10 cm x 10 cm x 40 cm, etc.) are subjected to underwater curing until the material age reaches 7 days. Next, the side lengths of the various concrete members are measured immediately after the underwater curing using a known method (for example, a comparator method, a contact gauge method, etc.). Next, the various concrete members are dried for a predetermined period of time (specifically, about 6 months) under predetermined conditions (specifically, a room temperature of 20°C and a humidity of 60%), and the side lengths of the various concrete members are measured after the drying. Then, whether or not the concrete members have excellent durability is judged based on whether or not the difference in the side lengths of the various concrete members before and after the drying is less than a threshold value (specifically, 900 μm).

[0106] (Test results of workability confirmation test and durability confirmation test - Durability confirmation test - Overview - Details of the composition of various concrete components) In addition, the various concrete members used in the durability confirmation test were the third concrete member, the fourth concrete member, and the sixth to ninth concrete members used in the workability confirmation test.

[0107] (Test results of workability confirmation test and durability confirmation test - Durability confirmation test - Details of test results) Next, the test results of the durability confirmation test will be described in detail.

[0108] As shown in Figure 5, the third concrete member, the fourth concrete member, and the sixth to ninth concrete members were below the threshold value. This confirmed that the third concrete member, the fourth concrete member, and the sixth to ninth concrete members have excellent durability.

[0109] (Test results of workability confirmation test and durability confirmation test - Summary of test results) From the above test results, the water-cement ratio is set to about 22% to 40%, and the unit weight of the steel fiber material is set to 38.75 kg / m 3 from 77.5 kg / m 3It was confirmed that it is effective to set the unit weight of the organic fiber material at about 1.0 kg / m 3 The unit weight of the admixture is 3.0 kg / m 3 from 12.24 kg / m 3 The degree and unit weight of the adhesion improver are 7.5 kg / m 3 from 198 kg / m 3 The effectiveness of keeping the ratio at a certain level was confirmed.

[0110] Furthermore, when the adhesion improver is silica fume, the water-cement ratio is set to about 22%, and the unit weight of the steel fiber material is set to 38.75 kg / m 3 The unit weight of the admixture is set at 9 kg / m 3 from 12.44 kg / m 3 The unit weight of silica fume is set at 22.5 kg / m 3 from 37.5 kg / m 3 In addition, when the adhesion improver is silica sand, the water-cement ratio is about 35%, and the unit weight of the steel fiber material is 54.6 kg / m 3 The unit weight of the admixture is set at 3.7 kg / m 3 The unit weight of the silica sand is set at 198 kg / m 3 The effectiveness of keeping the amount of

[0111] In addition to the above tests, compression tests and bending tests were conducted using known methods on concrete members No. 1 to No. 11. Although the results of these tests are omitted here, it was confirmed that all concrete members had the standard compressive and bending performance.

[0112] (Effects of the embodiment) Thus, according to the embodiment, the concrete mixture contains at least water, cement material, aggregate, admixture, organic fiber material, and steel fiber material, the water-cement ratio, which is the mixture ratio of water and cement material, is about 22% to 40%, and the unit weight of the steel fiber material is 38.75 kg / m 3 from 77.5 kg / m 3Therefore, the above test results show that the workability and durability of the concrete member 1 can be improved, and the manufacturability and usability of the concrete member 1 can be improved.

[0113] In addition, the unit weight of the organic fiber material is 1.0 kg / m 3 As a result of the above, compared to other unit weights, the decrease in the strength of the concrete member 1 at high temperatures can be suppressed, and the fire resistance of the concrete member 1 can be improved.

[0114] The unit weight of the admixture is 3.0 kg / m 3 from 12.24 kg / m 3 Therefore, the above test results show that, compared to other unit weights, the workability of the concrete member 1 can be improved, and the manufacturability of the concrete member 1 can be improved.

[0115] The unit weight of the adhesion improver is 7.5 kg / m 3 from 198 kg / m 3 Therefore, even when the water-cement ratio is relatively high, the adhesion of the cement material to the organic fiber material and / or the steel fiber material can be improved, and the strength of the concrete member 1 can be increased.

[0116] The adhesion improver is silica fume, the water-cement ratio is about 22%, and the unit weight of the steel fiber material is 38.75 kg / m 3 The unit weight of the admixture is set at 9 kg / m 3 from 12.44 kg / m 3 The unit weight of silica fume is set at 22.5 kg / m 3 from 37.5 kg / m 3 Therefore, the test results described below show that when the adhesion improving agent is silica fume, the workability and durability of the concrete member 1 can be improved, and the manufacturability and usability of the concrete member 1 can be improved.

[0117] The adhesion improver is silica sand, the water-cement ratio is about 35%, and the unit weight of the steel fiber material is 54.6 kg / m 3 The unit weight of the admixture is set at 3.7 kg / m 3 The unit weight of the silica sand is set at 198 kg / m 3 Therefore, the test results described below show that when the adhesion improving agent is silica sand, the workability and durability of the concrete member 1 can be improved, and the manufacturability and usability of the concrete member 1 can be improved.

[0118] In addition, since the steel fiber material contains plated steel fibers and / or stainless steel fibers, deterioration of the steel fiber material due to corrosion, etc. can be suppressed compared to other materials, and the functionality of the steel fiber material can be maintained.

[0119] [III] Modifications to the embodiment Although the embodiments of the present invention have been described above, the specific configurations and means of the present invention can be modified and improved as desired within the scope of the technical ideas of the inventions described in the claims. Such modifications will be described below.

[0120] (About the problem to be solved and the effects of the invention) First, the problems that the invention aims to solve and the effects of the invention are not limited to those described above, and the present invention may solve problems that are not described above or achieve effects that are not described above, or may solve only some of the problems that are described or achieve only some of the effects that are described.

[0121] (shape, number, structure, time series) The components illustrated in the embodiments and drawings may be modified and improved as desired within the scope of the technical concept of the present invention with respect to the shape, numerical values, or structure or chronological relationships of multiple components.

[0122] (Regarding concrete components) In the above embodiment, the concrete member 1 is described as including the reinforcing bars 20. However, the present invention is not limited to this, and for example, the reinforcing bars 20 may be omitted.

[0123] (About the main unit) In the above embodiment, the main body 10 is described as being configured to include an adhesion improving material, but this is not limiting, and for example, the adhesion improving material may be omitted.

[0124] (About admixtures) In the above embodiment, the admixture is described as a water-reducing agent, but is not limited thereto. For example, the admixture may include an air-entraining agent, a plasticizer, and / or a hardening accelerator in addition to the water-reducing agent.

[0125] (About organic fiber materials) In the above embodiment, the organic fiber material is described as polypropylene fiber, but the present invention is not limited to this, and may be, for example, a fiber material other than polypropylene fiber (for example, polyethylene fiber).

[0126] (Additional Note) The concrete member of Appendix 1 is a concrete member constituting a structure, and contains at least water, cement material, aggregate, admixture, organic fiber material, and steel fiber material, the water-cement ratio, which is the mixture ratio of the water and the cement material, is about 22% to 40%, and the unit weight of the steel fiber material is 38.75 kg / m 3 from 77.5 kg / m 3 That was the extent of it.

[0127] The concrete member of Appendix 2 is the concrete member of Appendix 1, wherein the unit weight of the organic fiber material is 1.0 kg / m 3 That's all.

[0128] The concrete member of Appendix 3 is the concrete member of Appendix 1 or 2, wherein the unit weight of the admixture is 3.0 kg / m 3 from 12.24 kg / m 3 That was the extent of it.

[0129] The concrete member of appendix 4 is the concrete member of appendix 1 or 2, further comprising an adhesion improver for improving adhesion of the cement material to the organic fiber material and / or the steel fiber material, and the unit weight of the adhesion improver is 7.5 kg / m 3 from 198 kg / m 3 That was the extent of it.

[0130] The concrete member of appendix 5 is the concrete member of appendix 4, wherein the adhesion improving agent is silica fume which constitutes a part of the cement material, the water-cement ratio is about 22%, and the unit weight of the steel fiber material is 38.75 kg / m 3 The unit weight of the admixture is about 9 kg / m 3 from 12.44 kg / m 3 The unit weight of the silica fume is about 22.5 kg / m 3 from 37.5 kg / m 3 That was the extent of it.

[0131] The concrete member of appendix 6 is the concrete member of appendix 4, wherein the adhesion improver is silica sand constituting a part of the aggregate, the water-cement ratio is about 35%, and the unit weight of the steel fiber material is 54.6 kg / m 3 The unit weight of the admixture is about 3.7 kg / m 3 The unit weight of the silica sand is about 198 kg / m 3 That was the extent of it.

[0132] The concrete member of Supplementary Note 7 is the concrete member of Supplementary Note 1 or 2, wherein the steel fiber material includes plated steel fiber and / or stainless steel fiber.

[0133] (Effect of supplementary notes) According to the concrete member described in Appendix 1, at least water, cement material, aggregate, admixture, organic fiber material, and steel fiber material are included, the water-cement ratio, which is the mixture ratio of water and cement material, is about 22% to 40%, and the unit weight of the steel fiber material is 38.75 kg / m 3 from 77.5 kg / m 3Therefore, as the test results described later show, it is possible to improve the workability and durability of the concrete member, and it is possible to improve the manufacturability and usability of the concrete member.

[0134] According to the concrete member described in Appendix 2, the unit weight of the organic fiber material is 1.0 kg / m 3 Since the above is the case, other unit weights (specifically, 1.0 kg / m 3 In comparison with a concrete member having a high temperature resistance (less than 1000° C.), the decrease in the strength of the concrete member at high temperatures can be suppressed, and the fire resistance of the concrete member can be improved.

[0135] According to the concrete member described in Appendix 3, the unit weight of the admixture is 3.0 kg / m 3 from 12.24 kg / m 3 Therefore, the test results described later show that compared with other unit weights, the workability of the concrete member can be improved, and the manufacturability of the concrete member can be improved.

[0136] According to the concrete member described in Appendix 4, the unit weight of the adhesion improving material is 7.5 kg / m 3 from 198 kg / m 3 Therefore, even when the water-cement ratio is relatively low, the adhesion of the cement material to the organic fiber material and / or the steel fiber material can be improved, and the strength of the concrete member can be increased.

[0137] According to the concrete member described in Appendix 5, the adhesion improver is silica fume, the water-cement ratio is about 22%, and the unit weight of the steel fiber material is 38.75 kg / m 3 The unit weight of the admixture is set at 9 kg / m 3 from 12.44 kg / m 3 The unit weight of silica fume is set at 22.5 kg / m 3 from 37.5 kg / m 3Therefore, the test results described below show that when the adhesion improving agent is silica fume, the workability and durability of the concrete member can be improved, and the manufacturability and usability of the concrete member can be improved.

[0138] According to the concrete member described in Appendix 6, the adhesion improver is silica sand, the water-cement ratio is about 35%, and the unit weight of the steel fiber material is 54.6 kg / m 3 The unit weight of the admixture is set at 3.7 kg / m 3 The unit weight of the silica sand is set at 198 kg / m 3 Therefore, the test results described later show that when the adhesion improving agent is silica sand, the workability and durability of the concrete member can be improved, and the manufacturability and usability of the concrete member can be improved.

[0139] According to the concrete member described in Appendix 7, the steel fiber material contains plated steel fiber and / or stainless steel fiber, so that deterioration of the steel fiber material due to corrosion, etc. can be suppressed compared to other materials, and the functionality of the steel fiber material can be maintained. [Explanation of symbols]

[0140] 1 Concrete materials 10 Main body 20 Steel Bars

Claims

1. A concrete member constituting a structure, The composition includes at least water, cementitious materials, aggregates, admixtures, organic fiber materials, and steel fiber materials; The water-cement ratio, which is the mixing ratio of the water and the cement material, is set to about 22% to 40%, The unit weight of the steel fiber material is 38.75 kg / m 3 From 77.5 kg / m 3 To a certain extent, Concrete components.

2. The unit weight of the organic fiber material is 1.0 kg / m 3 That's all. The concrete member according to claim 1.

3. The unit weight of the admixture is 3.0 kg / m 3 From 12.24 kg / m 3 To a certain extent, The concrete member according to claim 1 or 2.

4. The adhesive composition further comprises an adhesion promoter for enhancing adhesion of the cement material to the organic fiber material and / or the steel fiber material, The unit weight of the adhesion improving material is 7.5 kg / m 3 From 198 kg / m 3 To a certain extent, The concrete member according to claim 1 or 2.

5. The adhesion improver is silica fume that constitutes a part of the cement material, The water-cement ratio is about 22%, The unit weight of the steel fiber material is 38.75 kg / m 3 To an extent, The unit weight of the admixture is 9 kg / m 3 From 12.44 kg / m 3 To an extent, The unit weight of the silica fume is 22.5 kg / m 3 From 37.5 kg / m 3 To a certain extent, The concrete member according to claim 4.

6. The adhesion improver is silica sand constituting a part of the aggregate, The water-cement ratio is about 35%, The unit weight of the steel fiber material is 54.6 kg / m 3 To an extent, The unit weight of the admixture is 3.7 kg / m 3 To an extent, The unit weight of the silica sand is 198 kg / m 3 To a certain extent, The concrete member according to claim 4.

7. The steel fiber material includes plated steel fiber or / and stainless steel fiber, The concrete member according to claim 1 or 2.

Citation Information

Patent Citations

  • Method of estimating cracking load of high-strength fiber-reinforced concrete

    JP2010223761A